Kvantitativní změny IL- 6 ve spinálních gangliích laboratorního potkana po unilaterálním poškození sedacích nervů - Veselková, Zuzana (2009)
Neuropathic pain state can arise from peripheral nerve injury. Within cell bodies of injured primary sensory neurons in dorsal root ganglia there is induced changed gene expresion. The new molecular synthesis paterns involve altered cytokine expresion. A significant involvement of IL-6 protein in neuropathic pain induction and modulation of nerve regeneration is suggested from several lines of experimental studies. This study sought to evaluate both spatial and temporal changes of IL-6 protein levels in plasma and ipsi- and contralateral lumbal (L4-L5) dorsal root ganglia (DRG) after the lesion of peripheral nerve. Commercially available ELISA test (BioSource, CA, USA) was used for quantitative analysis of IL-6 protein. Male Wistar rats weighing (250-300 g) were divided into three groups: i/ non-operated animals (n=9) rats; ii/ the group underwent aseptic triple unilateral ligation of sciatic nerve (ScNL; n=36) with periods of survival for 1, 3, 7 and 14 days; iii/ operated group witho.